2017
DOI: 10.1111/lang.12247
|View full text |Cite
|
Sign up to set email alerts
|

The Processing of English Derived Words by Chinese‐English Bilinguals

Abstract: This study examined the sensitivity of Chinese‐English bilinguals to derivational word structure in English. In the first experiment, English monolinguals showed masked priming effects for prime‐target pairs related both transparently (e.g., hunter‐HUNT) and opaquely (e.g., corner‐CORN) but not for those related purely in terms of form (e.g., freeze‐FREE), whereas bilinguals showed priming in all three conditions. Furthermore, stronger form priming was found for bilinguals who were less experienced in English.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
49
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(86 citation statements)
references
References 37 publications
12
49
1
Order By: Relevance
“…In the present study, however, we found significant orthographic priming effects. This is more in line with previous research on non-native speakers (Diependaele et al, 2011;Feldman et al, 2010;Heyer & Clahsen, 2015;J. Li, Taft, et al, 2017;J.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, however, we found significant orthographic priming effects. This is more in line with previous research on non-native speakers (Diependaele et al, 2011;Feldman et al, 2010;Heyer & Clahsen, 2015;J. Li, Taft, et al, 2017;J.…”
Section: Discussionsupporting
confidence: 92%
“…*flexint-flex), or reduced, such as in speakers with lower proficiency (see J. Li, Taft, et al, 2017;Taft, Li, & Beyersmann, 2018), as may be the case of our Setswana speakers. However, we found priming for prime-target pairs that overlap word-initially (e.g.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Masked priming studies, for example, revealed efficient priming effects for both the head and the modifier components of compounds, and for both transparent and opaque compounds (Beyersmann et al., ; Duñabeitia, Laka, Perea, & Carreiras, ; Fiorentino & Fund‐Reznicek, ). Furthermore, studies comparing L1 and proficient L2 speakers found similar effects of decomposition of compounds for both speaker groups (González Alonso, Baquero Castellanos, & Müller, ; M. Li et al., ; Uygun & Gürel, ). Priming studies of inflection, on the other hand, have led to more variable outcomes.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, L2 processing of morphologically complex words has been found to be more susceptible to surface form prime–target overlap than L1 processing. Unlike L1 control groups, advanced bilinguals showed significant priming effects for orthographically related items in a number of masked priming experiments (Diependaele, Duñabeitia, Morris, & Keuleers, ; Feldman, Kostić, Basnight‐Brown, Đurđević, & Pastizzo, ; Heyer & Clahsen, ; J. Li, Taft, & Xu, ; M. Li, Jiang, & Gor, ).…”
Section: Background Literaturementioning
confidence: 99%